THE EFFECT OF DIGITAL MARKETING AND ELECTRONIC WORD OF MOUTH ON PURCHASE DECISIONS AND CUSTOMER SATISFACTION - Muhammad Azhar; Heru Tri Sutiono; Wisnalmawati Wisnalmawati (Seminar Nasional Informatika (SEMNASIF), 2021)
This research aims to analyze the influence of digital marketing and electronic word of mouth on the buying decision and customer’s satisfaction at Kappy Komputer, Yogyakarta. The population used in this research is Kappy Komputer’s customers, with 100 respondents used as sample measure, using probability sampling method, especially simple random sampling in particular. The data is collected by spreading questionnaire. Analysis technique used in this research is the PLS (Partial Least Square) analysis method. The result shows us that: 1) digital marketing influences buying decision in a good way. 2) There is positive influence of electronic word of mouth on the buying decision. 3) There is positive influence of digital marketing on the customer’s satisfaction. 4) There is no positive influence of electronic word of mouth on the customer’s satisfaction. 5) There is positive influence of buying decision on the customer’s satisfaction.